HMGB1/RAGE axis in tumor development: unraveling its significance - Fan, Anqi; Gao, Mengxiang; Tang, Xuhuan; Jiao, Mengya; Wang, Chenchen; Wei, Yingying; Gong, Quan; Zhong, Jixin (Frontiers in oncology, 2024)
High mobility group protein 1 (HMGB1) plays a complex role in tumor biology. When released into the extracellular space, it binds to the receptor for advanced glycation end products (RAGE) located on the cell membrane, playing an important role in tumor development by regulating a number of biological processes and signal pathways. In this review, we outline the multifaceted functions of the HMGB1/RAGE axis, which encompasses tumor cell proliferation, apoptosis, autophagy, metastasis, and angiogenesis. This axis is instrumental in tumor progression, promoting tumor cell proliferation, autophagy, metastasis, and angiogenesis while inhibiting apoptosis, through pivotal signaling pathways, including MAPK, NF-κB, PI3K/AKT, ERK, and STAT3. Notably, small molecules, such as miRNA-218, ethyl pyruvate (EP), and glycyrrhizin exhibit the ability to inhibit the HMGB1/RAGE axis, restraining tumor development. Therefore, a deeper understanding of the mechanisms of the HMGB1/RAGE axis in tumors is of great importance, and the development of inhibitors targeting this axis warrants further exploration.